The Impact of Risk Management on Financial Performance of Banks: The Case of Jordan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Scholars, professionals, and regulators regard efficient risk management as a pillar of bank management. The Basel Committee on Banks Regulation has introduced the Basel I Agreements, accompanied by the Basel II Agreements and recently the Basel III Agreement, to deal with this issue in the awareness of this circumstance and the need for the holistic approach to managing bank risk. Risk reduction is one of the determinants of banks' returns. Moreover, risk reduction, if practical, avoids or mitigates unnecessary threats and effectively controls the payouts. The latest global financial crisis taught us that risk reduction and implementation are necessary to achieve continued success objectives. The purpose of this study is to analyze Lebanese banks ' risk management policy and its effect on bank performance. This study investigates the impact of risk management practices on Lebanese banks' financial performance. Many banks had been facing risk management practices and default risks in loans because of the current financial and economic situations that Jordan is passing through. The research implemented the quantitative methodology by distributing the questionnaires to over 300 participants; however, only 123 respondents replied to them. The results were analyzed using regression analysis and proved a relationship between risk management and financial performance. The results showed a direct relationship between credit, liquidity, market risk, and financial performance. The findings showed that For every one unit increase in risk control, the risk financial performance is affected by 1%, while for every one unit increase in credit risk, the risk financial performance is affected by 1.6%, while for every one unit increase in market risk, the financial performance is affected by 1.5% and for every one-unit increase in liquidity risk the financial performance is affected by 4.7%.